Analysis of the Technological Position in Relation to Aluminium Casting Production - Pacana, Andrzej; Czerwińska, Karolina (Advances in Mechanical and Materials Engineering, 2023)
The dynamically developing production market, and in particular the metallurgic industry, enforces constant improvement of the level of production efficiency and product quality, which influences company position on the market and the level of its competitiveness. Therefore, the aim of the study was to determine the current position of the foundry enterprise, taking into account the aluminium gearbox casting, in the context of tech-nological capabilities and market position, as well as to identify critical factors and, finally, to indicate the conditions for its strengthening. The study used a 3x3 matrix. The company under study, in the context of manufacturing the analysed product, is classified in the area of "marketing improvement". This area demon-strates the need to take measures to establish a marketing and development department and the need to make better use of the company’s identified technological potential. The method presented in the study can be useful for analysing the position of manufacturing and service companies in various industries, in order to select an appropriate development strategy.